Analysis of the behaviour of social media users in the context of security risk reduction in the digital environment - Slavkovic, Ana; Slavkovic, Nikola; Subošić, Dane (Sociološki pregled, 2023)
This paper deals with the issues of the analysis of the behaviour of social media users in the context of security risk reduction in the digital environment. In this respect, the subject of this paper is the behaviour of social media users (mainly millennials, from the population of university students, attending studies in the field of security) depending on the gender. The aim of the research is to identify recommendations for a safer use of social media. To this end, the research was conducted on the basis of an anonymous survey comprising 15 questions (3 of demographic and 12 questions of essential significance). The survey covered 333 university students (undergraduate and graduate students of both genders) attending study programmes in the field of security. With the use of the Mann-Whitney test, contingency tables, the Kruskal-Wallis test, as well as the Spearman’s rank correlation test, it has been established that the behaviour patterns of men and women who use social media are very similar, but that there is a substantial statistical difference in certain scenarios. In addition to this, this survey has shown that, irrespective of the gender, risks of being attacked are consciously taken when sharing personal information, along with a reckless use of devices, passwords, and passcodes. By comparing the above-mentioned conclusions with the position of the general hypothesis: “There are similarities and differences between men and women in terms of the behaviour patterns on social media and in the cyberspace in general”, so the conclusion is that it is verified. One of the solutions to the identified problems in the behaviour of social media users is to raise their awareness regarding the risks of doing business and/or accessing entertainment content on social media, as well as their continuous training for the purpose of protecting their own data.
Keywords: cybersecurity; social media; data protection; gender; behaviour patterns